Feasibility of telephonic unblinding as part of a randomized controlled trial results dissemination plan in the South African context - Saxon, Bonnie Jeanne (My University, 2014)
The Good Participatory Practice Guidelines recommend that research results are made available to a broad range of stakeholders, including policy makers and trial participants, yet there is little guidance on how this may be achieved. The Microbicides Development Programme (MDP301 trial) was a large scale clinical trial that took place at thirteen clinics in South Africa, Tanzania, Uganda and Zambia between 2004 and 2009. The results of this trial were released in late 2009 and a comprehensive, multi-method results dissemination plan was implemented to communicate the research findings to policy makers, key stakeholders, research staff, Community Advisory Boards and trial participants between December 2009 and November 2010. This study was a retrospective analysis which included a process evaluation (and costing) of the implementation of the results dissemination plan for the MDP301 trial and an analysis of how the incorporation of telephonic unblinding potentially benefited the research community.
Submitted in partial fulfilment of the requirements for the degree of Master of Public Health, in the field of Social and Behaviour Change Communications, in the University of the Witwatersrand, Johannesburg, 2012
Keywords: Clinical Trials as Topic--methods; Clinical Trial